Pengembangan Media Pembelajaran Bahasa Arab Berbasis Web Educandy untuk Siswa SMP Cerdas Murni Tembung - Zulfahmi Lubis; Yasmin Harahap (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Learning media is a tool to facilitate teaching and learning.With the media can also increase student learning interest.Students are also more active and not only students, teachers also participate actively and creatively inteaching, because behind good and easy-to-understand learning media there are teachers whoactive and creative in making learning mediaThe purpose of this research is to develop educandy web-based learning media at Smart Pure Tembung Middle School. This research method uses the R&D technique proposed by Borg and Gall where researchers limit it to the best 7 steps: 1) problem identification; 2) data collection; 3) product design; 4) design validation; 5) product trials; 6) product revision; 7) wear test. This research is a media that is suitable for use as an evaluation medium for getting to know Arabic at the school stage. The validation results from media experts are with a percentage of 85% (very feasible). The use of educational media also received a "positive" reaction from 29 students in class VII-3 SMP Pure Intelligent Tembung with a percentage of 90% which shows an increase in students' interest and motivation in learning Arabic, and as much as 86% shows an interest in students' Arabic vocabulary mastery increasing. In this way, learning educandy web media is very feasible to be used in Arabic learning media. Keywords: Media, Arabic Language, Educandy